The relationship between Northern Khmer people and the forest: A study through ethnobotanical knowledge and vocabulary maintenance - Homchong, Napongchai; Ungsitipoonporn, Siripen; Simard, Candide (Ethnobotany Research and Applications, 2023)
Background: Northern Khmer speakers in five villages in Chuea Phloeng sub-district, Prasat district, Surin province, Thailand, are notable for being a Northern Khmer descendant community who have a long-standing and close relationship with the surrounding Takaw forest. This study examines the relationship between Northern Khmer speakers and the Takaw forest as documented ethnobotanical knowledge and vocabulary maintenance. Methods: The data collection was carried out among participants of two age groups, using quantitative and qualitative methods: a basic vocabulary test, an ethnobotanical knowledge test, which is based on the Traditional Knowledge and Language Vitality Index (Franco et al. 2015), and an interview to collect Northern Khmer basic vocabulary and plant names and their associated ethnobotanical knowledge. Results: The statistical analysis shows a significant weak correlation, suggesting that Northern Khmer speakers who have a high level of language proficiency are likely to have ethnobotanical knowledge at a high level. The transmission of knowledge typically starts in childhood, and family members serve as a primary source of knowledge. Children learn about plants and the forest through family activities that they engage in daily, taught by adults generally using the Northern Khmer language. Conclusions: The villagers’ experience with wild plants of the Takaw forest has been accumulated and passed down between generations through the use of the Northern Khmer language. This study contributes to a better understanding of how ethnobotanical knowledge is encoded in a language, and how both knowledge and language can be maintained for future generations. Keywords: Northern Khmer, language maintenance, ethnobotanical knowledge, community forest, cultural heritage